Solid slow-release carbon source as well as preparation and application thereof

The solid sustained-release carbon source is prepared by chemical cross-linking method of polyvinyl alcohol, octadecyl acrylate and other materials, which solves the problems of high carbon release rate and poor sustained-release effect in the prior art, and achieves stable carbon release rate and high efficiency Denitrification and nitrogen removal avoid secondary pollution.

CN119240936AActive Publication Date: 2025-01-03SICHUAN HYDROGEN CARBON & OXYGEN TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411583454.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-03
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing solid-state sustained-release carbon release rate is high, the sustained-release effect is poor, and the COD concentration in the effluent is not effectively controlled, resulting in secondary pollution.

Method used

Polyvinyl alcohol, octadecyl acrylate and ethyl orthosilicate are used to prepare solid state sustained release carbon source through chemical crosslinking method to form a network structure to stabilize the carbon source, and the controlled carbon release rate is 0.22mg/(g·h ) and ensure the mechanical strength and stability of the material through multiple freeze-thawing and chemical crosslinking.

Benefits of technology

The stable carbon release rate and efficient denitrification and nitrogen removal of solid state sustained-release carbon sources are achieved, avoiding COD concentration exceeding the standard, and ensuring the cleanliness of the water and environmental safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240936A_ABST
    Figure CN119240936A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-state slow-release carbon source and preparation and application thereof.The method comprises the steps that octadecyl acrylate is added into a polyvinyl alcohol solution, the mixture is heated and stirred at the temperature of 95 DEG C, and the carbon source is added and fully mixed for a reaction; slowly dropwise adding tetraethoxysilane into the mixed solution through a peristaltic pump; carrying out ultrasonic defoaming, pouring into a mold, naturally cooling to room temperature, freezing and forming at-20 DEG C, naturally unfreezing at room temperature, repeating the freezing-unfreezing operation, demolding, putting into a saturated boric acid solution containing CaCl2, and carrying out chemical crosslinking at 4 DEG C; and washing with ultrapure water, drying to constant weight at 60 DEG C, and then sealing and storing in an oxygen isolation manner. The problems that in the prior art, the carbon release rate is high, the slow release effect is poor, and the COD concentration of a water body cannot be controlled are solved, the carbon release rate can be stabilized at 0.22 mg / (g.h), the carbon release agent is used for denitrification nitrogen removal of the water body mainly containing nitrate nitrogen, the efficiency is high and stable, and the COD concentration of effluent can be well controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a slow-release carbon source for denitrification and denitrification, and in particular to a solid slow-release carbon source and a preparation method and application thereof. Background Art

[0002] The total amount control index of water environment includes COD, TP and ammonia nitrogen. Most sewage treatment facilities oxidize ammonia nitrogen in wastewater into nitrate before discharging it. In the non-point source pollution caused by surface runoff, the ammonia nitrogen in agricultural wastewater or domestic sewage is basically oxidized into nitrate because the surface runoff usually has a long confluence time and the water body is not deep. Whether it is the tail water of sewage treatment facilities or the non-point source pollution runoff, it will eventually enter the rivers and lakes. The large amount of nitrate nitrogen contained in it will still cause obvious harm to the river and lake ecosystems. Therefore, conducting research on denitrification of high nitrate nitrogen water bodies lays the foundation for including nitrate nitrogen or total nitrogen in the total amount control index, which is of great significance to completely improve the quality of the water environment.

[0003] Since the oxidation of ammonia nitrogen in water bodies usually occurs after the oxidation of COD, the COD concentration in water bodies with high nitrate nitrogen concentrations is usually extremely low. Existing nitrate nitrogen removal technologies mainly include short-range denitrification technologies that do not require an external carbon source and denitrification technologies that require an external carbon source. Among them, short-range denitrification technologies that do not require an external carbon source and synchronous denitrification technologies are not mature enough and have harsh implementation conditions. Therefore, the current mainstream technology still uses denitrification technology with an external liquid carbon source. Since solid slow-release carbon sources can not only save carbon source dosing equipment, but also serve as microbial attachment carriers to improve denitrification effects, in recent years, there has been a gradual upsurge in the research of solid slow-release carbon sources replacing liquid carbon sources for denitrification and denitrification. The preparation of solid slow-release carbon sources includes two methods: pyrolysis and chemical cross-linking. The solid slow-release carbon source obtained by pyrolysis is basically in the form of biochar, with high mechanical strength but complex preparation conditions, large yield fluctuations, and low utilization effect. The current main research direction is to prepare solid slow-release carbon sources by chemical cross-linking method to coat natural organic matter or organic synthetic materials. Solid slow-release carbon sources that can be applied in engineering applications require high mechanical strength, low carbon release rate, stable carbon release rate, good denitrification effect and no secondary pollution.

[0004] Existing document 1 (patent number is CN118005196A) proposes a high mechanical strength straw resource slow-release carbon source material. The invention uses a perforated acrylic ball as a carbon source carrier. Although the denitrification effect is good, there is a problem of serious COD exceeding the standard. Document 2 (patent number is CN118125612A) discloses a denitrification biological carrier and its preparation method based on iron agent, modified activated carbon, polycaprolactone, sodium dodecyl sulfate, hydrogel binder, and modified activated carbon is 3-chloro-2-hydroxypropyltrimethylammonium chloride modified activated carbon, but the COD concentration in the effluent cannot be guaranteed. Document 3 (patent number is CN118255461A) relates to a preparation method of a hydrogel-coated slow-release carbon source, and the material is prepared by natural polysaccharide materials as a whole, encapsulating various large and small molecular sugars and high molecular carbon sources, and the whole can be completely biodegraded, but the carbon release rate is high, and the carbon source is basically released in 24h, and the slow-release effect is not ideal. Summary of the invention

[0005] The purpose of the present invention is to provide a solid slow-release carbon source and its preparation and application, which solves the problems of high carbon release rate, poor slow-release effect and inability to control COD concentration in the prior art. The carbon release rate can be stabilized at 0.22 mg / (g·h), and is used for denitrification and denitrification of water bodies mainly composed of nitrate nitrogen. It is not only efficient and stable, but also can better control the effluent COD concentration to avoid secondary pollution.

[0006] In order to achieve the above object, the present invention first provides a method for preparing a solid slow-release carbon source, the method comprising:

[0007] (1) Add octadecyl acrylate to a polyvinyl alcohol solution, heat and stir at 95° C., add a carbon source and mix thoroughly to obtain a mixed solution. The carbon source is corn starch or acetate starch.

[0008] (2) Slowly add ethyl orthosilicate into the mixed solution using a peristaltic pump.

[0009] (3) Ultrasonic degassing: pouring the solution after ultrasonic degassing into a mold and naturally cooling it to room temperature, freeze-molding at -20°C, thawing it naturally at room temperature, and repeating the above freeze-thaw operation to obtain the molded material; demolding, and placing it in a saturated boric acid solution containing CaCl2, and chemically cross-linking it at 4°C.

[0010] (4) The cross-linked material was washed with ultrapure water, dried at 60° C. to constant weight, and then sealed and oxygen-proofed for storage to obtain a solid slow-release carbon source.

[0011] Preferably, in step (1), the mass ratio of polyvinyl alcohol to octadecyl acrylate in the polyvinyl alcohol solution is (5-20):1, and the molar ratio of polyvinyl alcohol to carbon source in the polyvinyl alcohol solution is (1-5):(1-5). Polyvinyl alcohol is a water-soluble polymer with excellent mechanical properties and mechanical properties. It is safe and non-toxic under certain conditions. After decomposition, it only produces carbon dioxide and water, and does not pollute the environment. It is an ideal material for modifying carbon sources. However, the hydroxyl groups in carbon sources such as starch and polyvinyl alcohol molecules are hydrophilic, which will cause the structure of the slow-release carbon source to be unstable. By modifying the hydroxyl groups, the stability of the material structure can be improved and the slow-release rate of the carbon source can be controlled. Octadecanyl acrylate has unique colloidal properties and high stability, which can improve the physical properties of polyvinyl alcohol. After the two are blended, a network-like carrier is formed, and the carbon source is connected by chemical bonds to form a slow-release carbon source. The chemical bonds are broken under hydrolysis or microbial decomposition to achieve the purpose of carbon slow release. The mass ratio of the two mixed affects the stability of the carrier structure and the pore size.

[0012] Preferably, in step (2), the volume mass ratio of the tetraethyl orthosilicate to the carbon source is (5-15) mL: 10 g, and the slow dripping speed of the tetraethyl orthosilicate is 10 mL / 3.5 h. When the volume mass ratio of the tetraethyl orthosilicate to the carbon source is (5-15) mL: 10 g, the prepared slow-release carbon source has complete coating, stable structure, good slow-release effect and good mechanical properties.

[0013] Preferably, in step (3), the freezing molding time is 24 hours; the chemical cross-linking time is 24 hours. The size of the mold is 1 cm 3 The concentration of CaCl2 in the saturated boric acid solution containing CaCl2 is 1-10%; the number of repeated freezing-thawing operations is 3 times.

[0014] More preferably, the concentration of CaCl2 in the saturated boric acid solution containing CaCl2 is 3%. Polyvinyl alcohol and boric acid are chemically cross-linked to form a network structure, and octadecyl acrylate and CaCl2 are cross-linked to form a network structure. 2+ Affinity also forms a network structure. The two network structures interweave with each other and wrap around the surface of the carbon source, reducing the hydrophilicity of the slow-release carbon source and further improving the structural stability.

[0015] Preferably, in step (4), the drying time is 24 hours.

[0016] The present invention provides a solid slow-release carbon source prepared by the preparation method.

[0017] Preferably, the carbon release rate of the solid slow-release carbon source is 0.22 mg / (g·h).

[0018] The present invention provides an application of the solid slow-release carbon source in denitrification.

[0019] Preferably, the application involves denitrification of water bodies contaminated with nitrate nitrogen.

[0020] The solid slow-release carbon source of the present invention and its preparation and application solve the problems of high carbon release rate, poor slow-release effect and inability to control COD concentration in the prior art, and have the following advantages:

[0021] 1. The solid carbon release rate prepared by the present invention can be stabilized at 0.22 mg / (g·h), and the amount of carbon source released can be efficiently utilized by microorganisms for denitrification by calculating the amount of carbon source added.

[0022] 2. Compared with the existing inventions, the solid slow-release carbon source of the present invention is used for denitrification of water bodies mainly composed of nitrate nitrogen. It is not only highly efficient and stable, but also can better control the COD concentration of the effluent to avoid secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a comparison chart of COD effluent concentration when YX-3 of Example 4 of the present invention and CX-3 of Example 1 are used for denitrification.

[0024] Figure 2 This is a comparison chart of nitrate nitrogen removal rates when YX-3 of Example 4 of the present invention and CX-3 of Example 1 are used for denitrification. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following examples, unless otherwise specified, all the drugs used were analytically pure and purchased from Chengdu Kelong Chemicals Co., Ltd. The instruments and equipment used are shown in Table 1.

[0027] Table 1 List of instruments and equipment

[0028]

[0029] Example 1

[0030] A method for preparing a solid slow-release carbon source, the method comprising:

[0031] (1) A 10% polyvinyl alcohol (PVA) solution was prepared, octadecyl acrylate (SA) was added to the PVA solution, and the solution was heated and stirred in a 95°C heat-collecting constant temperature heating magnetic stirrer for 2 h, and acetate starch was added and mixed and reacted for 2 h to obtain a mixed solution; wherein the mass ratio of PVA to octadecyl acrylate in the PVA solution was 4:5, and the mass ratio of PVA to starch in the acetate starch in the PVA solution was 1:5.

[0032] (2) Slowly adding tetraethyl orthosilicate into the mixed solution through a peristaltic pump (dropping rate: 10 mL / 3.5 h); wherein the mass ratio of starch to tetraethyl orthosilicate in the acetate starch is 1:1.

[0033] (3) Ultrasonic debubbling: pour the solution after ultrasonic debubbling into a 1 cm 3 The molded material was naturally cooled to room temperature in a cubic mold, frozen at -20°C for 24 hours, and then thawed naturally at room temperature for 2 hours, and the freezing-thawing operation was repeated twice; the molded material was then demolded and quickly placed in a saturated boric acid solution containing 3% CaCl2, and chemically cross-linked at 4°C for 24 hours;

[0034] (4) The cross-linked material was washed five times with ultrapure water to remove excess chemical cross-linking agent on the surface, dried in a 60°C constant temperature oven for 24 h until constant weight was achieved, and then sealed and oxygen-proofed for storage to obtain a solid-state slow-release carbon source, which was designated as CX-3.

[0035] Example 2

[0036] A method for preparing a solid slow-release carbon source is basically the same as that in the embodiment, except that: in step (1), the acetate starch is adjusted to corn starch, there is no step (2), and in step (3), no repeated freezing-thawing process is performed; after the same operation as in Example 1, the solid slow-release carbon source obtained is recorded as YS-NT.

[0037] Example 3

[0038] A method for preparing a solid slow-release carbon source is basically the same as that in the embodiment, except that: in step (1), the acetate starch is adjusted to corn starch, and in step (3), no repeated freezing-thawing process is performed; after the same operation as in Example 1, the solid slow-release carbon source obtained is recorded as YS-T.

[0039] Example 4

[0040] A method for preparing a solid slow-release carbon source is basically the same as that in the example, except that: in step (1), the acetate starch is adjusted to corn starch; after the same operation as in Example 1, the obtained solid slow-release carbon source is recorded as YS-3.

[0041] Comparative Example 1

[0042] A method for preparing a solid slow-release carbon source is basically the same as that in the example, except that: in step (1), no acetate starch is present (no carbon source is added); and the carbon source obtained by the same operation as in Example 1 is recorded as no carbon source is added.

[0043] Experimental Example 1 Verification of Carbon Release and Compressive Strength Performance of Solid Slow-Release Carbon Sources Prepared in Examples 1 to 4

[0044] 1. Carbon release

[0045] The carbon release process of the solid slow-release carbon source prepared in Examples 1 to 4 can be divided into a burst release period, a stable period and an end period. The carbon release process is mainly concentrated in the stable period, that is, the carbon release rate of the solid slow-release carbon source in the stable period can be stably lower. The higher the compressive strength of the solid slow-release carbon source, the better. The carbon release rate adopts the clean water static carbon release method to investigate the carbon release performance of the slow-release carbon source. The specific test method is: weigh 10g of the slow-release carbon source into a blue-mouth bottle, inject 500mL of distilled water and seal it with a cover, and at 25°C, take samples at certain intervals (0, 2, 4, 6, 8 and 10h) and replace the distilled water. Subsequently, replace the distilled water every 24h and measure the COD concentration in the water sample. The first-order kinetic equation and the second-order kinetic equation are used to describe the change of COD over time during the carbon release process, calculate and judge the carbon release rate of the slow-release carbon source, and the specific results are shown in Table 2.

[0046] Table 2 Comparison of carbon release rates of YS-NT of Example 2 and YS-T of Example 3

[0047]

[0048] It can be seen from Table 2 that the carbon release rate of YS-T in Example 3 is lower and the carbon release effect is better.

[0049] 2. Compressive strength

[0050] The compressive strength test method is: randomly select 30 complete sample materials, with no limit on size and mass, and use a digital push-pull dynamometer to vertically press each material until it produces an irreversible deformation or breaks, and record the value on the push-pull dynamometer, and use the average value to represent its compressive strength. The higher the compressive strength of the solid slow-release carbon source, the better, and the specific results are shown in Table 3.

[0051] Table 3 Comparison of compressive strength of YS-NT of Example 2 and YS-T of Example 3

[0052]

[0053] It can be seen from Table 3 that the compressive strength of YS-T in Example 3 is higher and the stability is better.

[0054] Experimental Example 2 Verification of the Denitrification Application of the Solid Slow-Release Carbon Source Prepared in Examples 1 to 4

[0055] The carbon source is selected to be a type that can be efficiently utilized by denitrifying bacteria, so that it can be efficiently utilized during denitrification and denitrification, avoiding the secondary pollution of COD caused by the release into the water body and not being utilized in time. The present invention applies the carbon source YX-3 of Example 4 and the carbon source CX-3 of Example 1 to denitrification and denitrification, and the specific method is as follows:

[0056] (1) Calculating the solid slow-release carbon source flow rate Q1 required for denitrification based on the amount of water to be treated and the nitrate content therein;

[0057] (2) Calculate the solid slow-release carbon source amount Q2 based on the microbial utilization rate of 75% in the denitrification process;

[0058] (3) Calculate the dosage M of the solid slow-release carbon source based on the carbon release rate of 0.22 mg / (g·h);

[0059] (4) Add a solid slow-release carbon source of mass M into a suitable container, then add the water to be denitrified and let it stand for 24 hours.

[0060] like Figure 1 As shown, the COD concentration comparison chart of the effluent when YX-3 of Example 4 and CX-3 of Example 1 are used for denitrification, wherein YX-3 is Example 4, CX-3 is Example 1, and the effluent without adding carbon source is Comparative Example 1. Figure 1 It can be seen that the COD effluent concentration in the denitrification experimental system with CX-3 added in Example 1 is basically maintained at about 20 mg / L; the denitrification experimental system with YX-3 added in Example 4 is stabilized at 20-50 mg / L after 10 days of the experiment. It can be seen that the slow-release carbon source of the present invention has good carbon release stability.

[0061] like Figure 2 As shown in the figure, the removal rate of nitrate nitrogen in Example 4 of the present invention and CX-3 of Example 1 are compared when used for denitrification, wherein YX-3 is Example 4, CX-3 is Example 1, and no carbon source is added as Comparative Example 1. Figure 2 It can be seen that the two slow-release carbon sources in Example 4 and Example 1 of the present invention are both conducive to microbial denitrification, and the nitrate nitrogen removal effect of CX-3 in Example 1 is better than that of YX-3 in Example 4.

[0062] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a solid slow-release carbon source, characterized in that: The method includes: (1) adding octadecyl acrylate to a polyvinyl alcohol solution, heating and stirring at 95° C., adding a carbon source and mixing and reacting the mixture to obtain a mixed solution; the carbon source is corn starch or acetate starch; (2) slowly adding ethyl orthosilicate to the mixed solution by a peristaltic pump; (3) ultrasonic degassing, pouring the solution after ultrasonic degassing into a mold and naturally cooling it to room temperature, freezing it at -20°C, thawing it naturally at room temperature, and repeating the above freezing-thawing operation to obtain a molded material; demolding and placing it in a saturated boric acid solution containing CaCl2, and chemically cross-linking it at 4°C; (4) The cross-linked material was washed with ultrapure water, dried at 60° C. to constant weight, and then sealed and oxygen-proofed for storage to obtain a solid slow-release carbon source.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of polyvinyl alcohol to octadecyl acrylate in the polyvinyl alcohol solution is (5-20):1, and the molar ratio of polyvinyl alcohol to carbon source in the polyvinyl alcohol solution is (1-5):(1-5).

3. The preparation method according to claim 1, characterized in that: In step (2), the volume mass ratio of the tetraethyl orthosilicate to the carbon source is (5-15) mL:10 g, and the slow dripping speed of the tetraethyl orthosilicate is 10 mL / 3.5 h.

4. The preparation method according to claim 1, characterized in that: In step (3), the size of the mold is 1 cm 3 The concentration of CaCl2 in the saturated boric acid solution containing CaCl2 is 3%; the number of freeze-thaw operations is 3 times.

5. The preparation method according to claim 1, characterized in that: In step (3), the freezing molding time is 24 hours; the chemical cross-linking time is 24 hours.

6. The preparation method according to claim 1, characterized in that: In step (4), the drying time is 24 hours.

7. A solid slow-release carbon source prepared by the preparation method according to any one of claims 1 to 6.

8. The solid slow-release carbon source according to claim 7, characterized in that: The carbon release rate of the solid slow-release carbon source reaches 0.22 mg / (g·h).

9. Use of the solid slow-release carbon source as claimed in claim 7 in denitrification.

10. The use according to claim 9, characterized in that: The application includes denitrification of water bodies contaminated with nitrate nitrogen.

Citation Information

Patent Citations

  • Preparation method of slow-release carbon source filter material taking starch and polyvinyl alcohol as substrates

    CN103964565A

  • Preparation method of PVA-EM bacterium carrier particles

    CN108315317A

  • Preparation method of slow-release carbon source with corncob as core base

    CN114656033A

  • Preparation method of slow-release carbon source filler

    CN115594300A

  • Composite carbon source for removing nitrogen component in wastewater and preparation method thereof

    CN118125600A